2022
DOI: 10.35864/evmd.1008860
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of OvHV-2 virus in small ruminants in Western Turkey

Abstract: Malignant catarrhal fever (MCF) is a fatal disease of ruminants and has a worldwide distribution. The MCF virus (MCFV) group has currently known to contain 10 members. Ovine gammaherpesvirus 2 (OvHV-2) is one of the members of MCFV group and has economically importance in cattle. Sheep is the reservoir host of OvHV-2 while domestic goat is naturally susceptible species, although infection is generally asymptomatic in goat. In this study, the presence of OvHV-2 was investigated in sheep and goats by hemi-nested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…The Detection of positive samples in the lambs by amplifying the POL and ORF75 tegument protein gene of OvHV-2 in this study corroborates the ndings of Li et al (1998), who reported that OvHV-2 could be transmitted horizontally to lambs in the herd and shed the virus at-5-6 months old [30]. Additionally, Li et al ( 2001) indicated that OvHV-2 can infect fetuses during pregnancy [27], as reported by Pekmez et al [24]. The ndings for the virus in different age groups suggest that the virus is endemic to the area, as reported by Mananguit et al in Philippines [31] and Khudhair in Iraq [14].…”
Section: Discussionsupporting
confidence: 87%
“…The Detection of positive samples in the lambs by amplifying the POL and ORF75 tegument protein gene of OvHV-2 in this study corroborates the ndings of Li et al (1998), who reported that OvHV-2 could be transmitted horizontally to lambs in the herd and shed the virus at-5-6 months old [30]. Additionally, Li et al ( 2001) indicated that OvHV-2 can infect fetuses during pregnancy [27], as reported by Pekmez et al [24]. The ndings for the virus in different age groups suggest that the virus is endemic to the area, as reported by Mananguit et al in Philippines [31] and Khudhair in Iraq [14].…”
Section: Discussionsupporting
confidence: 87%